Frequency of classic stereotypies in endurance horses - Muñoz-Alonzo, Lisandro E. (2015)
The objective of this study was to determine the frequency of classic stereotypies in endurance horses of Región Metropolitana (Chile) and the association of these abnormal behaviors with age and sex of the animals. All resident endurance horses from 8 equestrian centres of the Región Metropolitana were studied (n=107). A description of classic stereotipies (crib-biting, weaving and box-walking) was given to each horse keeper and then they were asked for this presence or absence, along the name, sex, age and breed, of every horse under their care. To analyze the data, horses were divided by age into 3 groups: 3 to 6 years (n=28), 7 to 9 years (n=42) and 10 to 18 years (n=37). Based on their sex, they were divided into 3 groups: stallions (n=11), geldings (n=64) and mares (n=32). Results are expressed as percentages. Fisher`s test with p < 0.05 was used for statistical analysis of the variables age and sex. A 12.2% of all horses presented stereotypies: crib-biting (0.9%), weaving (6.5%) and box-walking (4.7%). No relationship was found between the presence of stereotypies and variables age and sex. This study evidence a high frequency of classic stereotypies in endurance horses of Región Metropolitana, mostly weaving, and no found association between classic stereotypies and the variables age and sex of horses.